KARAKTERISTIK TEKSTUR DAN WARNA KOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) DENGAN KOMBINASI KOTORAN SAPI MENGGUNAKAN Mikoroorganisme Selulotik (MOS) - YOSITA SUCI ARINI; DENO OKALIA; ANGGA PRAMANA; WAHYUDI WAHYUDI (Universitas Riau, 2019)
This research aims to know the characteristics of the texture and colour of compost from empty palm bunches(TKKS) and cow dung using selulotic microorganism (MOS). This research had been carried out in thevillage of Serosah, district of Hulu Kuantan, Kuantan Singingi Regency. Design used in this study was arandomized complete design (RAL) non factorial, which consists of 6 treatment and three replicates, namelyA0 (20 kg of TKKS + 200 ml of MOS), A1 (18 kg of TKKS + 2 kg of cow dung + 200 ml of MOS), A2 (16 kg ofTKKS + 4 kg of cow dung + 200 ml of MOS), A3 (14 kg of TKKS + 6 kg of cow dung + 200 ml of MOS), A4 (12kg of TKKS + 8 kg of cow dung + 200 ml of MOS), A5 (10 kg of TKKS + 10 kg of cow dung + 200 ml of MOS).Data from observation of each treatment were descriptively analyzed. Based on the results of the study it canbe concluded that the use of the empty palm bunches of compost by using cow and selulotic microorganisms(MOS) significantly affected the texture of the compost (a soft and slightly damp) and black in colour of10YR/21.